2008
DOI: 10.3402/ljm.v4i4.4839
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Value of EGFR and P53 Immunostaining in Tumors of the Urinary Bladder

Abstract: Abstract; The expression of EGFR and p53 has not been adequately studied as a prognostic tool in urinary bladder tumors. We analyzed 74 bladder cancer samples from Egypt for EGFR and p53 expression using immunohistochemistry. The tumors were of different histological types, grades and clinical stages, and with established lymph node status. Almost 61% of the tumors showed positive membranous EGFR expression and 74.3% had positive nuclear staining of p53. Analysis of correlation of the IHC staining with clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…They reported that the commonest affected age of presentation of urothelial cell carcinoma of bladder is 50 to 70 years Bladder urothelial cell carcinoma revealed negative expression of p53 in 15 (37.5%) of high grade samples, and positive expression of p53 in 7 (17.5%) too. While 14 (35%) of low grade sample show negative expression of p53 and 4 (10%) show positive of p53 expression, concluded that there are no association between expression of p53 and grade of tumor show (p value=0.449), This result consist by Ibrahim et al [13]. Others against reported significant correlation with higher grades [14,15,16,17].…”
Section: Discussionmentioning
confidence: 77%
“…They reported that the commonest affected age of presentation of urothelial cell carcinoma of bladder is 50 to 70 years Bladder urothelial cell carcinoma revealed negative expression of p53 in 15 (37.5%) of high grade samples, and positive expression of p53 in 7 (17.5%) too. While 14 (35%) of low grade sample show negative expression of p53 and 4 (10%) show positive of p53 expression, concluded that there are no association between expression of p53 and grade of tumor show (p value=0.449), This result consist by Ibrahim et al [13]. Others against reported significant correlation with higher grades [14,15,16,17].…”
Section: Discussionmentioning
confidence: 77%
“…In this study, though the frequency of p53 expression was higher for higher stage tumours, statistical significance was nil. But, this relation was proved by studies conducted by Ibrahim et al 14 and Galmozzi et al 15…”
Section: Discussionmentioning
confidence: 91%